Sex differences in the prevalence and hemodynamic profiles of hypertensive phenotypes: the HELIUS study. (25th November 2020) - Collard, D; Akchikchi, S; Snijder, M.B; Westerhof, B.E; Valkengoed, I.G.M; Vogt, L; Van Den Born, B.J.H
Abstract: Background: Based on systolic (SBP) and diastolic blood pressure (DBP), patients with hypertension can be classified into different phenotypes. Earlier studies have shown clear sex-differences in the relation between phenotype and cardiovascular outcomes, but large studies addressing underlying sex-differences in hemodynamics are lacking. Purpose: To examine sex differences in the prevalence and underlying hemodynamic profile of different hypertensive phenotypes. Methods: We used cross-sectional data of 22.112 individuals, 57.8% female, aged between 18–70 years from the HEalthy LIfe in an Urban Setting (HELIUS) study, an ongoing large multi-ethnic prospective cohort study. Based on office BP patients were classified as having: normal (NBP; SBP <140 mmHg and DBP <90 mmHg), isolated systolic hypertension (ISH; SBP ≥140 and DBP <90 mmHg), isolated diastolic hypertension (IDH; SBP <140 and DBP ≥90mmHg) or combined systolic diastolic hypertension (SDH; SBP ≥140 and DBP ≥90 mmHg). We explored sex differences in the prevalence hypertension and the distribution of phenotypes using chi-squared tests after stratification for age (young: <50, old: ≥50 years). In a subgroup of 11.046 participants, continuous non-invasive measurements of cardiac output (CO), stroke volume (SV), systemic vascular resistance (SVR) and mean arterial pressure (MAP) were obtained during 3–5 minutes with finger photoplethysmography in the supine position (Nexfin, Edwards Lifesciences, Irvine, CA, USA). Sex-differences between hemodynamic parameters were assessed using ANOVA tests of linear regression models correcting for age. Results: In young participants, the overall prevalence of hypertension was significantly higher in men (19.7%) compared to women (11.4%), with a different distribution of phenotypes (both p<0.001). Amongst young hypertensive participants, SDH was the most prevalent phenotype in both men (46%) and women (52%), ISH had a prevalence of respectively 23% in men and 26% in women. In older subjects, overall prevalence of hypertension was 40.2% in men and 35.9% in women (p<0.001), with a different phenotypical distribution (p<0.001). SDH was the most predominant phenotype in men (50%), whilst ISH was the most prevalent phenotype in women (55%). Both young and old participants with ISH showed an elevated cardiac output, ranging from 0.38–0.47 ml/min compared to normotensives. Older men with SDH and IDH had both elevated SVR and CO, while older women had only an elevation in SVR (Figure 1). Conclusions: There are important age-dependent sex-differences in the prevalence of hypertension, which translate into a different hemodynamic profile. The pattern of cardiac output alterations across phenotypes was different between older men and women, suggesting sex differences in the underlying pathophysiology of elevated blood pressure. These findings contribute to a better understanding of the pathogenesis of hypertension and could impact treatment responses. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): The Academic Medical Center (AMC) of Amsterdam and the Public Health Service of Amsterdam (GGD Amsterdam) provided core financial support for HELIUS. The HELIUS study is also funded by research grants of the Dutch Heart Foundation (Hartstichting; grant no. 2010T084), the Netherlands Organization for Health Research and Development (ZonMw; grant no. 200500003), the European Integration Fund (EIF; grant no. 2013EIF013) and the European Union (Seventh Framework Programme, FP-7; grant no. 278901).